2022
DOI: 10.1038/s42003-022-03266-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered regulation of mesenchymal cell senescence in adipose tissue promotes pathological changes associated with diabetic wound healing

Abstract: Pathologic diabetic wound healing is caused by sequential and progressive deterioration of hemostasis, inflammation, proliferation, and resolution/remodeling. Cellular senescence promotes wound healing; however, diabetic wounds exhibit low levels of senescent factors and accumulate senescent cells, which impair the healing process. Here we show that the number of p15INK4B + PDGFRα + senescent mesenchymal cells in adipose tissue increases transiently during early phases of wound healing in both non-diabetic mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Since positive correlations between NOTCH3 (but not with NOTCH1) and myofibrogenic-related gene expression were observed in human and mouse AT, it is strongly suggested that NOTCH3 is also the active Notch receptor in AT myofibrogenesis although gene editing approaches will permit to clearly state about the molecular identity of porting the hypothesis that NOTCH activity contributes to the depot-specific enrichment of −/CD271 + subsets that we previously reported (Esteve et al, 2019). Our findings also suggest that it will be worthwhile to investigate the role of NOTCH3 in wound healing, especially in light of a recent study describing that insufficient induction of AT senescence after injury is a pathological mechanism of diabetic wound healing (Kita et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Since positive correlations between NOTCH3 (but not with NOTCH1) and myofibrogenic-related gene expression were observed in human and mouse AT, it is strongly suggested that NOTCH3 is also the active Notch receptor in AT myofibrogenesis although gene editing approaches will permit to clearly state about the molecular identity of porting the hypothesis that NOTCH activity contributes to the depot-specific enrichment of −/CD271 + subsets that we previously reported (Esteve et al, 2019). Our findings also suggest that it will be worthwhile to investigate the role of NOTCH3 in wound healing, especially in light of a recent study describing that insufficient induction of AT senescence after injury is a pathological mechanism of diabetic wound healing (Kita et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, the group of patients with the highest progenitor senescence in VsAT is characterized by higher −/CD271 + premyofibroblast accumulation, supporting the hypothesis that NOTCH activity contributes to the depot‐specific enrichment of −/CD271 + subsets that we previously reported (Esteve et al, 2019). Our findings also suggest that it will be worthwhile to investigate the role of NOTCH3 in wound healing, especially in light of a recent study describing that insufficient induction of AT senescence after injury is a pathological mechanism of diabetic wound healing (Kita et al, 2022).…”
Section: Discussionmentioning
confidence: 62%
“…PDGF‐AA promotes myofibroblast differentiation, which is necessary for the wound closure process. [ 110 ] Studies have revealed that the duration of senescence is a key factor in the instance of transient, or temporary, senescence. The transient dynamics of senescence is beneficial in tissue repair because it allows for the recognition of damaged tissue by the immune system.…”
Section: Drawbacks Of Senescent Cell Eliminationmentioning
confidence: 99%
“…As shown in Figure C, compared to DM-Control, there was an increased ratio of proinflammatory (M1) to anti-inflammatory (M2) macrophages in the DM-NOX gel group at day 6, which was in close resemblance to the skin of Non-DM wounds (Figure S9). Chronic inflammation is a critical factor in nonhealing wounds and is characterized by the release of proinflammatory cytokines such as IL-6 and TNF-α. , The results revealed that the levels of IL-6 and TNF-α were significantly lower in the NOX-gel-treated wounds compared to those in the untreated wounds (Figure D,E). Additionally, the expression of the anti-inflammatory cytokine IL-10 was the highest in the NOX-gel-treated group (Figure F).…”
mentioning
confidence: 91%
“…Chronic inflammation is a critical factor in nonhealing wounds and is characterized by the release of proinflammatory cytokines such as IL-6 and TNF-α. 31,32 The results revealed that the levels of IL-6 and TNF-α were significantly lower in the NOX-gel-treated wounds compared to those in the untreated wounds (Figure 3D,E). Additionally, the expression of the anti-inflammatory cytokine IL-10 was the highest in the NOX-gel-treated group (Figure 3F).…”
mentioning
confidence: 95%